2009
DOI: 10.1007/s00373-009-0866-4
|View full text |Cite
|
Sign up to set email alerts
|

Directed Hamilton Cycle Decompositions of the Tensor Products of Symmetric Digraphs

Abstract: A Hamiltonian decomposition of G is a partition of its edge set into disjoint Hamilton cycles. Manikandan and Paulraja conjectured that if G and H are Hamilton cycle decomposable circulant graphs with at least one of them is nonbipartite, then their tensor product is Hamilton cycle decomposable. In this paper, we have proved that, if G is a Hamilton cycle decomposable circulant graph with certain properties and H is a Hamilton cycle decomposable multigraph, then their tensor product is Hamilton cycle decomposa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The above corollary shows how to “blow up the holes” in a Ct ${\overrightarrow{C}}_{t}$‐factorizaton by either keeping the cycle length, or “blowing up” the cycle length by the same odd factor. Note that Statement (b) also follows from [19, Lemma 2.11], and Statement (a) can be obtained from [20, Corollary 5.7] by appropriately orienting each cycle.…”
Section: Some Useful Decompositionsmentioning
confidence: 99%
“…The above corollary shows how to “blow up the holes” in a Ct ${\overrightarrow{C}}_{t}$‐factorizaton by either keeping the cycle length, or “blowing up” the cycle length by the same odd factor. Note that Statement (b) also follows from [19, Lemma 2.11], and Statement (a) can be obtained from [20, Corollary 5.7] by appropriately orienting each cycle.…”
Section: Some Useful Decompositionsmentioning
confidence: 99%
“…Moreover, a resolvable 2k-cycle decomposition of K m × K n and a decomposition of K m × K n into closed trails of length k have been studied in [33,34]. Besides that, Hamilton cycle decompositions of the graphs [8,[28][29][30][31]35]. Hence K m × K n is proved to be an important proper spanning subgraph of the regular complete…”
Section: Introductionmentioning
confidence: 99%
“…The problem of finding hamiltonian decompositions of product graphs is not new. hamiltonian decompositions of various product graphs, including digraphs, have been studied by many authors; see, for example, [1,6,9,10,11,13,14,15,16,18,17]. It has been conjectured [6] that if both G and H are hamiltonian decomposable graphs, then G H is hamiltonian decomposable, where denotes the cartesian product of graphs.…”
Section: Introductionmentioning
confidence: 99%
“…Hamiltonian decompositions of the tensor products of complete bipartite graphs and complete multipartite graphs are dealt with in [15]. Also in [17], Paulraja and Sivasankar proved that (K r × K s ) * , ((K r • K s ) × K n ) * , ((K r × K s ) × K m ) * , ((K r • K s ) × (K m • K n )) * and (K r,r × (K m • K n )) * are directed hamiltonian decomposable. It can be observed that K r , K r, r , K r •K s are circulant graphs.…”
Section: Introductionmentioning
confidence: 99%